Determinism and petitionary prayer in John and the Dead Sea Scrolls: ideological reading of John and the rule of community (1QS) - Tukasi, Emmanuel O. (Library of Second Temple studies, 2008)
Tukasi explores the theme of the determinism as articulated in the Rule of the Community and the Fourth Gospel with the aim of uncovering the relevance of petitionary prayer within the framework of the determinism of each book. Chapter one sets out the background against which the themes of determinism and petition in 1QS and John should be understood. Chapter two explores the nature of the determinism in the 1QS. The determinism is cosmological, soteriological, and eschatological. Chapter three demonstrates that the contents of the petitions are in harmony with the determinism articulated in